Geometry of stationary flows of liquid in vicinity of the high gradient ferromagnetic packing in constant external magnetic field - Gorobets, Svetlana; Gorobets, Oksana; Bondar, Natalia (My University, 2000)
The flows of electrolytes in the vicinity of ferromagnetic particles in a constant magnetic field have been investigated.
Keywords: високо градієнтні магнітні поля; высоко градиентные магнитные поля; high gradient magnetic fields; дисперсні частинки; дисперсные частицы; dispersed particles; кафедра готельно-ресторанної справи